Efeitos do método canguru nas habilidades orais e alimentação de prematuros - Ciochetto, Carla Ribeiro (2021)
The Kangaroo Mother Care (KMC) is considered a natural, cost-effective, evidence-based intervention, and is recommended as a standard of care for preterm neonates. The full-time presence of the mother in the kangaroo unit, by encouraging breastfeeding, can reduce the difficulties for oral feeding, which are frequent in preterm neonates, since sucking at the breast contributes to the development of the functions and structures of the stomatognathic system. This research aimed to verify the effects of KMC on oral skills, breastfeeding and introduction of complementary feeding in preterm neonates throughout the first year of life. This is a longitudinal observational, prospective and analytical study. The sample comprised 46 preterm neonates with gestational age at birth ≤ 34 weeks, allocated to the Kangaroo Neonatal Intermediate Care Unit (UCINCa) and the Conventional Neonatal Intermediate Care Unit (UCINCo) of a university hospital in southern Brazil. After neonatal discharge, participants were followed-up by telephone calls at 4, 6 and 12 months of corrected age. In preterm neonates who attended the UCINCa the maturation process of oral skills was faster, which translated into fewer days to make the transition from tube feeding to full oral feeding (4.5 days versus 10 days, for UCINCa and UCINCo, respectively, p=0.041). There was no influence on length of stay, although there was a reduction of 4 days in the length of stay, counted from the release of the oral route, in preterm neonates in the UCINCa. The KMC favored exclusive breastfeeding at hospital discharge, and significantly, at 4 months of corrected age, when 35% of preterm neonates were still on exclusive breastfeeding, and only 8.3% of children exiting the UCINCo. At 6 and 12 months of corrected age the rates of breastfeeding did not differ between units. The introduction of complementary feeding was reported in 45% and 42.3% of the infants in the UCINCa and UCINCo, respectively, at 4 months of corrected age. It was concluded that admission to the UCINCa accelerated the maturation process of oral skills in preterm neonates, shortening the time of transition from tube feeding to full oral feeding. In addition, it provided a significant increase in exclusive breastfeeding rates at neonatal discharge and at 4 months of corrected age. Participation in KMC was not protective on breastfeeding rates from the 6th month of corrected age, nor to avoid early introduction of complementary feeding.